2023
DOI: 10.1111/vco.12892
|View full text |Cite
|
Sign up to set email alerts
|

The animal's microbiome and cancer: A translational perspective

Abstract: Cancer is a substantial global health problem both in humans and animals with a consistent increase in mortality and incidence rate. The commensal microbiota has been involved in the regulation of several physiological and pathological processes, both within the gastrointestinal system and at distant tissue locations. Cancer is not an exception, and different aspects of the microbiome have been described to have anti‐ or pro‐tumour effects. Using new techniques, for example high‐throughput DNA sequencing, micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 262 publications
0
1
0
Order By: Relevance
“…Due to the considerable diversity of the bacterial biota and its intricate interactions with the intestinal epithelium, the examination of the biological community of intestines poses challenges [ 26 ]. Recent studies have demonstrated that the microbiotic environment of the gut and its functions in dogs and cats are similar to those in humans [ 30 ]. Short-chain fatty acids (SCFAs) produced by these microbes are indispensable for energizing the colon lining cells and supporting microbial metabolic functions.…”
Section: Normobiosis and Dysbiosismentioning
confidence: 99%
“…Due to the considerable diversity of the bacterial biota and its intricate interactions with the intestinal epithelium, the examination of the biological community of intestines poses challenges [ 26 ]. Recent studies have demonstrated that the microbiotic environment of the gut and its functions in dogs and cats are similar to those in humans [ 30 ]. Short-chain fatty acids (SCFAs) produced by these microbes are indispensable for energizing the colon lining cells and supporting microbial metabolic functions.…”
Section: Normobiosis and Dysbiosismentioning
confidence: 99%
“…The parasite-cancer relationship, both putative and confirmed, was observed in a range of domestic (dog, cats, ruminants, rats, mice, and poultry species) and wild or exotic species (prosimians, New-World and Old-World monkeys, snakes, and muskrats). A total of 15 parasite genera were identified, with the majority (14) being metazoan, especially (but not exclusively) helminths. The parasitic species identified were trematodes (C. sinensis, Fasciola spp., O. viverrini, Platynosomum illiciens, S. mansoni), cestodes (T. taeniformis), nematodes (G. pulchrum, S. lupi, Heterakis spp., Nochtia nochti, Ollulanus trichuspis, Ophidascaris sp., Trichinella spp.…”
Section: Parasites Associated With Neoplasia In Domestic and Wild Ani...mentioning
confidence: 99%
“…The oncologic burden is increasing in veterinary medicine as well [12], and the list of pathogens responsible for animal cancer development continues to grow [13,14]. In addition to various viral [15], putative bacterial species [16], and transmissible tumor cells [17][18][19] that cause cancer, certain parasites have also been identified over the years, although an overlooking of their impact on animal health was suggested [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%